PENERAPAN TECHNOBREEDING DAN TECHNOFEEDING BERBASIS KEARIFAN LOKAL DI DESA SIDOMULYO PENGASIH KULON PROGO - Setyo Utomo; Nur Rasminati (DHARMA BAKTI, 2018)
This activity aims to increase the economic empowerment of society through the application of appropriate technology and culture, held in 2 (two) groups of animals, Ngudi Rahayu and Sub Ngudi Rahayu, the number of participants are 15 people. Stages of activities starting from counseling, training, demonstration plots and mentoring. Activities that have been implemented are the economic empowerment goat breeders Ettawa crossbreed through continuous improvement of feed based on local resources are cheap and easy to obtain as well as the application of breeding technology. The results that have been achieved are demonstration plots of forage preservation was fermented using rice microbes and nutrients from a variety of ingredients such as fish, bamboo shoots, banana, turmeric, ginger, garlic and so on. Members of the group have been able to carry out the manufacture of rice microbial and sources of nutrients from a variety of organic materials available in the region. It was concluded that the villagers Sidomulyo represented by 2 groups of goat breeding business has implemented the concept of goat farm in a modern business through the use of local materials are available cheap, easily obtainable. Breeders also have understand the importance of good quality breed sources in order to improve the income communities.